Evaluating Semantic Knowledge Through a Semantic Association Task in Individuals With Dementia. (17th April 2020) - Luzzatti, Claudio; Mauri, Ilaria; Castiglioni, Stefania; Zuffi, Marta; Spartà, Chiara; Somalvico, Francesco; Franceschi, Massimo
Conceptual knowledge is supported by multiple semantic systems that are specialized for the analysis of different properties associated with object concepts. Various types of semantic association between concrete concepts—categorical (CA), encyclopedic (EA), functional (FA), and visual-encyclopedic (VEA) associations—were tested through a new picture-to-picture matching task (semantic association task, SAT). Forty individuals with Alzheimer's disease (AD), 13 with behavioral variant of frontotemporal dementia (bv-FTD), 6 with primary progressive aphasia (PPA), and 37 healthy participants were tested with the SAT. Within-group comparisons highlighted a global impairment of all types of semantic association in bv-FTD individuals but a disproportionate impairment of EA and FA, with relative sparing of CA and VEA, in AD individuals. Single-case analyses detected dissociations in all dementia groups. Conceptual knowledge can be selectively impaired in various types of neurodegenerative disease on the basis of the specific cognitive process that is disrupted.